Sulfur-tolerant shift catalyst and preparation method thereof

By introducing columnar montmorillonite materials and active components into the catalyst, the cobalt-molybdenum cerium columnar montmorillonite structure is formed, and the problem of methanation side reaction under high CO content and low water-gas ratio is solved, achieving efficient mass-transfer and heat transfer performance of the catalyst and safe and stable operation of the device.

CN119701986AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311262425.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

Under process conditions with high CO content and low water-gas ratio, when the temperature of the catalyst bed is higher than 350°C, a side reaction of methanation will occur, resulting in a decrease in product yield and an increase in safety risks. It is difficult for the prior art to effectively suppress this reaction.

Method used

By introducing column-supported montmorillonite materials and introducing active components and additives into the montmorillonite layers through chemical modification, a cobalt-molybdenum cerium column-supported montmorillonite structure is formed, which enhances the thermal conductivity and mass-transfer and heat transfer properties of the catalyst, thereby reducing the occurrence of methanation side reactions.

Benefits of technology

It effectively reduces the occurrence of methanation side reactions, avoids the safety risks brought by methanation reactions, reduces effective gas consumption, achieves the safe and smooth operation of the device, and has good economic benefits and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701986A_ABST
    Figure CN119701986A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sulfur-tolerant shift catalyst, which comprises the following steps: 1) dissolving a cobalt soluble salt and a lanthanide series metal soluble salt in a first solvent, heating to 60-80 DEG C to obtain a solution A, dissolving an ammonium molybdate salt in a second solvent, and heating to 60-80 DEG C to obtain a solution B; 2) adding calcium-based montmorillonite powder into the solution A, adding the solution B into the solution A, adding tetrabutyl titanate, curing at 60-80 DEG C, drying at 100-150 DEG C, and crushing to 180-200 meshes to obtain pillared montmorillonite; and (3) adding an aluminum-containing compound and magnesium oxide powder into the pillared montmorillonite, adding a binder, uniformly kneading, carrying out extrusion molding, drying, and roasting at 500-550 DEG C to obtain the sulfur-tolerant shift catalyst. The preparation method of the catalyst is simple, easy to implement and high in mass and heat transfer capacity, methanation side reactions can be effectively reduced, safety risks caused by the methanation reaction are avoided, effective gas consumption is reduced, and safe and stable operation of a device is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a sulfur-resistant conversion catalyst for preparing chemical raw materials such as synthesis gas, hydrogen and methanol from heavy raw materials such as coal and petroleum coke, and a preparation method thereof. Background Art

[0002] Co-Mo sulfur-resistant shift catalyst has excellent sulfur resistance and high activity for CO shift reaction, and has been applied on a large scale in the field of coal chemical industry. With the development of coal gasification process, the CO content in process gas is getting higher and higher. Under the process conditions of high CO content and low water-gas ratio, when the catalyst bed temperature is higher than 350℃, methanation side reaction will occur, and as the bed temperature increases, the methanation side reaction will gradually intensify, resulting in reduced product output and the risk of overheating. For gasification processes with low water-gas ratios such as Shell pulverized coal gasification and GSP gasification, methanation side reaction troubles the manufacturers, especially in the start-up stage, the water-gas ratio is not easy to control, and it is more likely to cause overheating or even overheating due to methanation side reaction. At present, the design unit mainly relies on controlling different shift process conditions to avoid the conditions for methanation side reaction, so as to suppress or avoid the occurrence of methanation side reaction, but methanation side reaction is still inevitable in actual application.

[0003] Montmorillonite is a kind of clay that can absorb a large amount of water and expand significantly in volume. Its silicon oxide layer contains a large number of hydroxyl groups. Pillared montmorillonite material is a porous material with a two-dimensional pore structure formed by introducing target organic or inorganic substances into the montmorillonite interlayer by chemical modification method using the exchangeable properties of cations or molecules between montmorillonite mineral layers and exchanging metal cations in montmorillonite. It has the characteristics of large specific surface area, high surface activity, regular distribution and adjustable pore size.

[0004] The invention patent application of Chinese Patent Publication No. CN116060071A discloses a high thermal conductivity sulfur-resistant conversion catalyst and a preparation method thereof, wherein a certain amount of SiC is placed in a container, and a certain amount of ethanol and a surfactant are added to obtain a first mixture; a certain amount of a high specific surface area carrier precursor is mixed with the first mixture, and stirred for 1-24 hours to form a second mixture; a certain amount of water, nitric acid, and ethanol are mixed to obtain a third mixture, and the third mixture is slowly dripped into the second mixture, and the temperature is increased and stirred until the ethanol is completely evaporated to obtain a colloidal solid; the colloidal solid is dried and roasted to obtain a catalyst carrier; a certain amount of a molybdenum source and a cobalt source are taken, dissolved in water to obtain two solutions, the two solutions respectively containing molybdenum and cobalt, and then the catalyst carrier is successively impregnated with the two solutions, followed by drying and roasting to obtain the sulfur-resistant conversion catalyst. The catalyst of this patent mainly relies on the thermal conductivity and semiconductor properties of SiC to achieve rapid electron transfer. By using a high specific surface area carrier for coating and modification, the specific surface area of ​​the catalyst is increased, thereby achieving a double improvement in thermal conductivity and catalytic performance. It is suitable for isothermal transformation processes, but for conventional sulfur-resistant transformation processes and reactors, it cannot solve the problem of methanation side reactions.

[0005] The invention patent of Chinese patent publication number CN116116424A discloses a preparation method of a bifunctional sulfur-resistant shift catalyst, comprising kneading pseudo-boehmite powder and magnesium material; after kneading, adding a binder, a dispersant and a pore-enlarging agent to continue kneading, wherein the magnesium material is one or a combination of any multiple of magnesium oxide, magnesium carbonate, magnesium hydroxide and magnesium nitrate, and the binder is one or a combination of any multiple of sesbania powder, sodium carboxymethyl cellulose, high alumina cement, bentonite and hydroxypropyl methylcellulose; after the kneaded materials are kneaded uniformly, a molybdenum source is added; , cobalt source, rare earth metal, metal additive and deionized water are configured into a clear solution, and then added to a kneader for kneading; the kneaded material is put into an extruder for extrusion, and then dried, and a mesh belt kiln is used for drying; the dried product is sprayed with citric acid solution through a spraying production line, and the spraying amount of citric acid solution is 60-105kg per ton of catalyst. The product is transported on the spraying production line for no less than 4.5 hours, and is transported to a secondary drying device for secondary drying while spraying. After the secondary drying is completed, the catalyst is roasted to obtain the catalyst. The catalyst in this patent is prepared by a new preparation process, which has a simple preparation process and low cost, and has both transformation and hydrolysis functions, but it cannot play a good inhibitory effect on the methanogenic side reaction. Summary of the invention

[0006] Based on the problems of the prior art, the present invention provides a sulfur-resistant shift catalyst and a preparation method thereof, which are simple and easy to implement, and have strong mass transfer and heat transfer capabilities. Compared with the current industrial sulfur-resistant shift catalysts, under the same conditions, the occurrence of methanation side reactions can be effectively reduced, the safety risks brought by the methanation reaction can be avoided, the effective gas consumption can be reduced, and the safe and stable operation of the device can be achieved, which has good economic benefits and application prospects.

[0007] The technical solution provided by the present invention is as follows: A first aspect of the present invention provides a method for preparing a sulfur-tolerant shift catalyst, comprising: 1) dissolving a soluble salt of cobalt and a soluble salt of a lanthanide metal in a first solvent, heating the solution to 60-80° C. to obtain a solution A, dissolving an ammonium salt of molybdenum acid in a second solvent, heating the solution to 60-80° C. to obtain a solution B; 2) Then, calcium-based montmorillonite powder is added to the solution A and stirred evenly, the solution B is added to the solution A and stirred evenly, and then tetrabutyl titanate is added and stirred evenly, and the mixture is aged at 60-80° C., dried at 100-150° C., and then crushed to 180-200 mesh to obtain pillared montmorillonite containing active components and additives; 3) adding aluminum-containing compound powder and magnesium oxide powder to the pillared montmorillonite powder, mixing evenly, adding a proper amount of binder and kneading evenly, extruding into a shape, performing a second drying, and calcining at 500-550° C. to obtain a sulfur-resistant shift catalyst; Wherein, in step 1), the amount of the soluble salt of cobalt added is 1%-8% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.2%-4% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 4%-12% of the mass of the catalyst calculated as molybdenum oxide; In step 2), the amount of calcium-based montmorillonite added is 20%-30% of the catalyst mass; In step 3), the aluminum-containing compound powder is 30%-45% of the catalyst mass in terms of aluminum oxide; and the magnesium oxide added is 10%-15% of the catalyst mass.

[0008] Preferably, in step 1), the soluble salt of cobalt is nitrate and / or acetate.

[0009] Preferably, in step 1), the soluble salt of the lanthanide metal is a nitrate.

[0010] Preferably, in step 1), the ammonium salt of molybdenum acid is ammonium molybdate.

[0011] Preferably, in step 1), the amount of the soluble salt of cobalt added is 2%-4% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.5%-1.5% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 6.5%-9.0% of the mass of the catalyst calculated as molybdenum oxide.

[0012] Preferably, in step 2), the pH of the calcium-montmorillonite is 7.5-8.5.

[0013] Preferably, in step 3), the mass ratio of magnesium oxide to aluminum oxide added is 1:2.0-4.5.

[0014] Preferably, the binder is citric acid, and the amount of the binder added is 3%-5% of the mass of the catalyst.

[0015] Preferably, the calcination time is 2-4 hours.

[0016] The second aspect of the present invention provides a sulfur-resistant shift catalyst prepared by the above preparation method.

[0017] The beneficial effects of the present invention include at least: The present invention provides a sulfur-resistant conversion catalyst and a preparation method thereof, which are simple and easy to implement. The catalyst introduces a pillared montmorillonite material, and introduces active components and additives into the montmorillonite interlayer by chemical modification to form a pillared montmorillonite (especially cobalt-molybdenum-cerium pillared montmorillonite) structure, so that the active components are dispersed in the montmorillonite interlayer, and the active metals are dispersed in the montmorillonite interlayer, which is beneficial to the reaction and the conduction of reaction heat, thereby enhancing the thermal conductivity of the catalyst, strengthening the mass transfer and heat transfer performance of the catalyst carrier, and reducing the hot spot temperature inside the catalyst pores. At the same time, the hydrophilic groups between the montmorillonite interlayers are utilized to increase the water vapor content between the layers, and the mass transfer and heat transfer capacity of the catalyst is stronger. Compared with the current industrial sulfur-resistant conversion catalyst, under the same conditions, it can effectively reduce the occurrence of methanation side reactions, avoid the safety risks brought by the methanation reaction, reduce the effective gas consumption, and realize safe and stable operation of the device, and has good economic benefits and application prospects.

[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the pressurized activity evaluation device in the test example.

[0020] Figure 2 This is a chromatogram of the tail gas after the physicochemical performance and pressurized activity test of the sulfur-resistant catalyst in Example 1 of the present invention.

[0021] Figure 3This is the chromatogram of the tail gas after the physical and chemical performance and pressurized activity test of the conventional sulfur-resistant catalyst QCS-03.

[0022] Description of Reference Numerals Figure 1 : 1. Raw gas purifier; 2. Pressure reducer; 3. Mixer; 4. Pressure gauge; 5. Shutdown valve; 6. Heating furnace; 7. Reaction tube; 8. Thermocouple tube in tube; 9. Condenser; 10. Separator; 11. Drainer; 12. Wet flow meter; 13. Vaporizer; 14. Water tank; 15. Water metering pump. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Examples of the embodiments are shown in the accompanying drawings. It should be understood that the specific embodiments described in the following embodiments of the present invention are only exemplary descriptions of the specific embodiments of the present invention, and are intended to be used to explain the present invention, but do not constitute a limitation of the present invention.

[0024] The endpoints of the scope disclosed in this article and any value are not limited to this accurate scope or value, and these scopes or values ​​should be understood as comprising values ​​close to these scopes or values.For numerical range, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article.In the description of the application, unless otherwise stated, the meaning of similar words such as "one / a kind", "multiple / multiple" is two / kinds or more than two / kinds.

[0025] A first aspect of the present invention provides a method for preparing a sulfur-tolerant shift catalyst, comprising: 1) dissolving a soluble salt of cobalt and a soluble salt of a lanthanide metal in a first solvent, heating the solution to 60-80° C. to obtain a solution A, dissolving an ammonium salt of molybdenum acid in a second solvent, heating the solution to 60-80° C. to obtain a solution B; 2) Then, calcium-based montmorillonite powder is added to the solution A and stirred evenly, the solution B is added to the solution A and stirred evenly, and then tetrabutyl titanate is added and stirred evenly, and the mixture is aged at 60-80° C., dried at 100-150° C., and then crushed to 180-200 mesh to obtain pillared montmorillonite containing active components and additives; 3) adding aluminum-containing compound powder and magnesium oxide powder to the pillared montmorillonite powder, mixing evenly, adding a proper amount of binder and kneading evenly, extruding into a shape, performing a second drying, and calcining at 500-550° C. to obtain a sulfur-resistant shift catalyst; Wherein, in step 1), the amount of the soluble salt of cobalt added is 1%-8% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.2%-4% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 4%-12% of the mass of the catalyst calculated as molybdenum oxide; In step 2), the amount of calcium-based montmorillonite added is 20%-30% of the catalyst mass; In step 3), the aluminum-containing compound powder is 30%-45% of the catalyst mass in terms of aluminum oxide; and the magnesium oxide added is 10%-15% of the catalyst mass.

[0026] In some preferred embodiments of the present invention, in step 1), the soluble salt of cobalt is nitrate and / or acetate. More preferably, the soluble salt of cobalt is cobalt nitrate.

[0027] In some preferred embodiments of the present invention, in step 1), the soluble salt of the lanthanide metal is a nitrate. More preferably, the soluble salt of the lanthanide metal is cerium nitrate.

[0028] In some preferred embodiments of the present invention, in step 1), the ammonium salt of molybdenum acid is ammonium molybdate.

[0029] In some preferred embodiments of the present invention, in step 1), the first solvent is deionized water to facilitate subsequent ion exchange and drying.

[0030] In some preferred embodiments of the present invention, in step 1), the second solvent is deionized water to facilitate subsequent ion exchange and drying.

[0031] According to the present invention, in step 1), the temperature of solution A obtained by heating is 60-80°C, specifically, for example, 60°C, 65°C, 70°C, 78°C, 80°C and any value in the range formed by any two of these point values.

[0032] According to the present invention, in step 1), the temperature of solution B obtained by heating is 60-80°C, specifically, for example, 60°C, 65°C, 70°C, 78°C, 80°C and any value in the range formed by any two of these point values.

[0033] In the present invention, the sulfur-resistant catalyst made of calcium-based montmorillonite is used, and the calcium salt in the catalyst is not easy to be lost, and the methanogenic side reaction can be effectively reduced. The inventors found that if sodium-based montmorillonite is used, the sodium salt in the catalyst is easy to be lost, which promotes the methanogenic side reaction, and the outlet CH4 content is too high, which cannot achieve the purpose of the present invention. Please refer to Comparative Example 3 and data.

[0034] In some preferred embodiments of the present invention, the pH value of the calcium-montmorillonite is 7.5-8.5, specifically, for example, it can be 7.5, 7.8, 7.9, 8.0, 8.4, 8.5 and any value in the range formed by any two of these values.

[0035] According to the present invention, in step 2), the solution B is added to the solution A, and any method can be used as long as it can be added uniformly, and the preferred method is dropwise addition.

[0036] According to the present invention, in step 2), the temperature is maintained at 60-80°C for aging, specifically, for example, it can be 60°C, 65°C, 70°C, 75°C, 78°C, 80°C and any value in the range formed by any two of these values.

[0037] According to the present invention, in step 2), the ripening time can be selected within a wide range, such as 2-10 hours, preferably 3-8 hours, specifically, for example, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours and any value in the range formed by any two of these point values.

[0038] According to the present invention, in order to remove moisture from the material to facilitate subsequent catalyst crushing, in step 2), the first drying temperature ranges from 100 to 150°C, preferably 120°C.

[0039] According to the present invention, in step 2), the particles are crushed to 180-200 meshes. Particles that are too large or too small are not suitable for the catalyst molding of the present invention and are not conducive to the formation of a pore structure.

[0040] In some preferred embodiments of the present invention, in step 1), the amount of the soluble salt of cobalt added is 2%-4% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.5%-1.5% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 6.5%-9.0% of the mass of the catalyst calculated as molybdenum oxide.

[0041] In some preferred embodiments of the present invention, in step 3), the aluminum-containing compound is pseudo-boehmite.

[0042] In some preferred embodiments of the present invention, in step 3), the mass ratio of magnesium oxide to aluminum oxide added is 1:2.0-4.5.

[0043] According to the present invention, in step 3), the binder is an acid, such as at least one of citric acid, nitric acid and oxalic acid.

[0044] In some preferred embodiments of the present invention, the binder is citric acid and the amount of the binder added is 3%-5% of the mass of the catalyst.

[0045] In some preferred embodiments of the present invention, in order to avoid affecting the pore structure of the catalyst, in step 3), the second drying is carried out by natural drying at room temperature.

[0046] According to the present invention, in step 3), the catalyst can be extruded into different shapes, such as strips, as required.

[0047] According to the present invention, in step 3), calcination is mainly for forming a stable catalyst support structure.

[0048] In some preferred embodiments of the present invention, the calcination time is 2-4 hours.

[0049] The second aspect of the present invention provides a sulfur-resistant shift catalyst prepared by the above preparation method.

[0050] The raw materials used in the following examples and comparative examples are all commercially available products, and the amount of raw materials added is calculated based on the preparation of 100 g of catalyst.

[0051] Example 1 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 14 g of cobalt nitrate and 1.52 g of cerium nitrate in 150 mL of deionized water and heat to 75°C to obtain solution A. Dissolve 10.4 g of ammonium molybdate in 100 mL of deionized water and heat to 75°C to form solution B. 2) Then, 24 g of calcium-based montmorillonite powder with a pH value of 7.8 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 53.1 g of tetrabutyl titanate was added and stirred evenly, and the temperature was maintained at 75° C. for aging for 6 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 55.3 g of pseudo-boehmite powder and 12 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.2, mix evenly, add 35 mL of an aqueous solution containing 3 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0052] Example 2 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 10 g of cobalt nitrate and 0.95 g of cerium nitrate in 140 mL of deionized water and heat to 60°C to obtain solution A. Dissolve 9.76 g of ammonium molybdate in 120 mL of deionized water and heat to 60°C to form solution B. 2) Then, 20 g of calcium-based montmorillonite powder with a pH value of 7.5 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 63.7 g of tetrabutyl titanate was added and stirred evenly, and the temperature was maintained at 60° C. for aging for 8 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 62.9 g of pseudo-boehmite powder and 10 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:4.4, mix evenly, add 40 mL of an aqueous solution containing 4 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 500°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0053] Example 3 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 16 g of cobalt nitrate and 2.65 g of cerium nitrate in 160 mL of deionized water and heat to 78°C to obtain solution A. Dissolve 7.9 g of ammonium molybdate in 100 mL of deionized water and heat to 78°C to form solution B. 2) Then, 28 g of calcium-based montmorillonite powder with a pH value of 8.4 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 42.5 g of tetrabutyl titanate was added and stirred evenly, and the temperature was maintained at 78° C. for 4 h, and the mixture was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 70.2 g of aluminum gel powder and 15 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:2.3, mix evenly, add 30 mL of an aqueous solution containing 5 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 550°C for 2 h to obtain a finished sulfur-resistant shift catalyst.

[0054] Example 4 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 8 g of cobalt nitrate and 1.33 g of cerium nitrate in 120 mL of deionized water and heat to 80°C to obtain solution A. Dissolve 11.0 g of ammonium molybdate in 120 mL of deionized water and heat to 80°C to form solution B. 2) Then, 30 g of calcium-based montmorillonite powder with a pH value of 7.9 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 38.3 g of tetrabutyl titanate was added and stirred evenly, and the temperature was kept at 80° C. for aging for 3 h, and the mixture was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 54.7 g of pseudo-boehmite powder and 11 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.5, mix evenly, add 40 mL of an aqueous solution containing 3.5 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 520°C for 3 h to obtain a finished sulfur-resistant shift catalyst.

[0055] Example 5 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 12.8 g of cobalt nitrate and 1.90 g of cerium nitrate in 140 mL of deionized water and heat to 70°C to obtain solution A. Dissolve 9.5 g of ammonium molybdate in 100 mL of deionized water and heat to 70°C to form solution B. 2) Then, 25 g of calcium-based montmorillonite powder with a pH value of 8.0 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 34.0 g of tetrabutyl titanate was added and stirred evenly, and the temperature was kept at 70° C. for aging for 5 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 58.6 g of pseudo-boehmite powder and 14 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:2.9, mix evenly, add 45 mL of an aqueous solution containing 4.5 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 3 h to obtain a finished sulfur-resistant shift catalyst.

[0056] Comparative Example 1 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 14 g of cobalt nitrate and 1.52 g of cerium nitrate in 150 mL of deionized water and heat to 75°C to obtain solution A. Dissolve 10.4 g of ammonium molybdate in 100 mL of deionized water and heat to 75°C to form solution B. 2) Then, 35 g of calcium-based montmorillonite powder with a pH value of 7.8 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 53.1 g of tetrabutyl titanate was added and stirred evenly, and the temperature was maintained at 75° C. for aging for 6 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 43.4 g of pseudo-boehmite powder and 9.3 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.2, mix evenly, add 35 mL of an aqueous solution containing 3 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0057] Comparative Example 2 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 14 g of cobalt nitrate and 1.52 g of cerium nitrate in 150 mL of deionized water and heat to 75°C to obtain solution A. Dissolve 10.4 g of ammonium molybdate in 100 mL of deionized water and heat to 75°C to form solution B. 2) Then, 24 g of calcium-based montmorillonite powder with a pH value of 7.8 was added to solution A, and the mixture was stirred evenly. Solution B was added dropwise to solution A, and the mixture was stirred evenly. The mixture was aged at 75° C. for 6 h, and then dried at 120° C. and crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives. 3) Add 55.3 g of pseudo-boehmite powder, 12 g of light magnesium oxide powder and 12.5 g of titanium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.2, mix evenly, add 35 mL of an aqueous solution containing 3 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0058] Comparative Example 3 1) Dissolve 14 g of cobalt nitrate and 1.52 g of cerium nitrate in 150 mL of deionized water and heat to 75°C to obtain solution A. Dissolve 10.4 g of ammonium molybdate in 100 mL of deionized water and heat to 75°C to form solution B. 2) Then, 24 g of sodium montmorillonite powder with a pH value of 7.8 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 53.1 g of tetrabutyl titanate was added and stirred evenly, and the temperature was kept at 75° C. for aging for 6 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 55.3 g of pseudo-boehmite powder and 12 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.2, mix evenly, add 35 mL of an aqueous solution containing 3 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0059] Comparative Example 4 The method for preparing a sulfur-resistant shift catalyst comprises the following steps: 1) Dissolve 14 g of cobalt nitrate and 1.52 g of cerium nitrate in 150 mL of deionized water and heat to 75°C to obtain solution A. Dissolve 10.4 g of ammonium molybdate in 100 mL of deionized water and heat to 75°C to form solution B. 2) Then, 24 g of calcium-based montmorillonite powder with a pH value of 7.0 was added to solution A and stirred evenly, solution B was added dropwise to solution A and stirred evenly, and then 53.1 g of tetrabutyl titanate was added and stirred evenly, and the temperature was maintained at 75° C. for aging for 6 h, and the solution was first dried at 120° C. and then crushed to 180-200 mesh to obtain cobalt-molybdenum-cerium pillared montmorillonite containing active components and additives; 3) Add 55.3 g of pseudo-boehmite powder and 12 g of light magnesium oxide powder to the above pillared montmorillonite powder, wherein the mass ratio of magnesium oxide to aluminum oxide is 1:3.2, mix evenly, add 35 mL of an aqueous solution containing 3 g of citric acid, knead evenly, extrude into strips, dry naturally, and calcine at 530°C for 4 h to obtain a finished sulfur-resistant shift catalyst.

[0060] Test Example 1 Physical and chemical properties and pressure activity test of sulfur-tolerant shift catalyst: use Figure 1 The catalysts prepared in the above examples and comparative examples were tested for their physicochemical properties and pressurized activity using the pressurized activity evaluation device and evaluation conditions shown in the figure. Figure 1 The device is used to simulate industrial conditions, measure the carbon monoxide concentration and its changes in the tail gas of the "original particle size" catalyst under different conditions, compare the conversion activity and stability of the catalyst, and comprehensively evaluate the various properties of the catalyst. The reaction tube is a stainless steel tube with a thermocouple tube in the center. A certain amount of water is added according to the requirements of different water-gas ratios. After high-temperature gasification, it enters the reaction tube together with the raw gas to carry out the water-gas shift reaction. The tail gas after the reaction is analyzed by chromatography. The chromatograms of the tail gas after the physicochemical properties and pressurized activity tests of the sulfur-resistant catalyst of Example 1 and the conventional sulfur-resistant catalyst QCS-03 are shown respectively. Figure 2 and Figure 3 , the chromatographic test results are shown in Table 2 and Table 3 respectively.

[0061] Specific evaluation criteria include: The catalyst loading volume was 50 mL; The sulfur-tolerant shift catalyst sulfurization conditions are as follows: Sulfide gas composition: CO content: 50.0%; H2S content: ~0.3%; balance: H2; Pressure: 2.0MPa; Dry gas air velocity: 1000h -1 ;H2S content: ~0.3%; Vulcanize at 250℃ for 4h, then increase the temperature to 300℃ for 3h, then increase the temperature to 350℃ for 2h.

[0062] The pressure evaluation conditions for the sulfur-tolerant shift catalyst are as follows: Raw gas composition: CO content: 65.0%; H2S content: ~0.1%; balance: H2; Inlet temperature: 250℃; Pressure: 4.0MPa; Water / gas: 0.4; Dry gas air velocity: 2000h -1 ; Time: 20h; The catalyst pressurized activity was taken as the average value of stable data. The results are shown in Table 1.

[0063] The comparison sample is the conventional sulfur-resistant catalyst QCS-03 (produced by Shandong Qilu Keli Chemical Research Institute Co., Ltd.).

[0064] Table 1 Physical and chemical properties of sulfur-resistant catalysts and pressure evaluation results .

[0065] It can be seen from Table 1 that the physicochemical properties and pressurized activities of catalysts prepared with different ratios are different, especially the catalyst strength, specific surface area and outlet methane content.

[0066] The amount of calcium-based montmorillonite powder used in Comparative Example 1 is high, and the catalyst strength is significantly reduced; tetrabutyl titanate is not used in Comparative Example 2, and the specific surface area is significantly reduced; in Comparative Example 3, calcium-based montmorillonite is not used, but sodium-based montmorillonite is used, which has a certain promoting effect on the methanation side reaction, resulting in an excessively high CH4 content at the outlet; the pH of the calcium-based montmorillonite in Comparative Example 4 is 7.0. Although the catalyst strength is increased, the specific surface area is reduced, which has a significant promoting effect on the methanation side reaction, and the CH4 content at the outlet is too high.

[0067] In particular, under the same conditions, the methane content at the outlet of the sulfur-resistant catalyst of the embodiment of the present invention is significantly lower than that of the conventional sulfur-resistant catalyst QCS-03 and the sulfur-resistant catalyst of the comparative example. The sulfur-resistant catalyst of the present invention can significantly reduce the methanation side reaction.

[0068] Table 2 The chromatographic test results of tail gas after the physicochemical performance and pressurized activity test of the sulfur-resistant catalyst in Example 1 of the present invention .

[0069] Table 3 Comparative conventional sulfur-resistant catalyst QCS-03 was tested for physicochemical properties and pressurized activity. .

[0070] Comparison of the results in Tables 2 and 3 further shows that the methane content at the outlet of the sulfur-resistant catalyst of the embodiment of the present invention is significantly lower than that of the conventional sulfur-resistant catalyst QCS-03 for comparison, and the sulfur-resistant catalyst of the present invention can significantly reduce the methanation side reaction.

[0071] Test Example 2 Thermal conductivity test of sulfur-resistant catalyst: The thermal conductivity of the sulfur-resistant catalyst was measured using a thermal conductivity meter (DRL-11). The specific process is as follows: first, read the reading on the scale before loading the sample, then remove the pressure plate, and apply a thin layer of thermal grease on the end faces of the upper and lower hot electrodes and the upper and lower surfaces of the sulfur-resistant catalyst sample; place the sample between the upper and lower hot electrodes for shaft assembly, lower the reflective screen, and then tighten the screws on the pressure plate by mechanical force to make the sulfur-resistant catalyst sample in close contact with the upper and lower hot end surfaces, read the reading on the scale again, and subtract the reading on the scale before loading the sample from the reading on the scale to obtain the actual thickness of the sulfur-resistant catalyst sample; set the temperature of the external constant temperature water bath to 40℃±0.1℃, and turn on the circulation switch; turn on the host power switch, start the computer, and enter the DRL thermal conductivity test program. Set the temperature of the hot electrode and start heating: enter the cross-sectional area and thickness of the sulfur-resistant catalyst sample in the program, turn on the heating switch, and measure the thermal conductivity; by changing the temperature of the heater, the thermal conductivity of the sulfur-resistant catalyst sample is tested, and the results are shown in Table 4.

[0072] Table 4 Thermal conductivity of sulfur-resistant catalyst .

[0073] The above performance test results show that compared with the comparative example and the existing conventional sulfur-resistant shift catalyst, the sulfur-resistant shift catalyst prepared in the embodiment of the present invention has a higher thermal conductivity and stronger mass transfer and heat transfer capabilities.

[0074] The catalyst of the present invention disperses the active components between the montmorillonite layers to form a pillared montmorillonite structure. The interlayer structure uses reactants and products to pass more quickly. At the same time, the active metal is more conducive to the reaction heat transfer generated by its reaction than the carrier, thereby improving the heat and mass transfer performance of the catalyst as a whole. In addition, the thermal conductivity of the catalyst will be affected by the carrier, and different carriers have different thermal conductivity of the catalyst. What the present invention can do is that under the same conditions of the carrier, the thermal conductivity of the catalyst of the present invention is maximized by technical means.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and do not constitute a limitation on the content of the present invention. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a sulfur-tolerant shift catalyst, characterized in that: include: 1) dissolving a soluble salt of cobalt and a soluble salt of a lanthanide metal in a first solvent, heating the solution to 60-80° C. to obtain a solution A, dissolving an ammonium salt of molybdenum acid in a second solvent, heating the solution to 60-80° C. to obtain a solution B; 2) Then, calcium-based montmorillonite powder is added to the solution A and stirred evenly, the solution B is added to the solution A and stirred evenly, and then tetrabutyl titanate is added and stirred evenly, and the mixture is aged at 60-80° C., dried at 100-150° C., and then crushed to 180-200 mesh to obtain pillared montmorillonite containing active components and additives; 3) adding aluminum-containing compound powder and magnesium oxide powder to the pillared montmorillonite powder, mixing evenly, adding a proper amount of binder and kneading evenly, extruding into a shape, performing a second drying, and calcining at 500-550° C. to obtain a sulfur-resistant shift catalyst; Wherein, in step 1), the amount of the soluble salt of cobalt added is 1%-8% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.2%-4% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 4%-12% of the mass of the catalyst calculated as molybdenum oxide; In step 2), the amount of calcium-based montmorillonite added is 20%-30% of the catalyst mass; In step 3), the aluminum-containing compound powder is 30%-45% of the catalyst mass in terms of aluminum oxide; and the magnesium oxide added is 10%-15% of the catalyst mass.

2. The preparation method according to claim 1, characterized in that: In step 1), the soluble salt of cobalt is nitrate and / or acetate.

3. The preparation method according to claim 1, characterized in that: In step 1), the soluble salt of the lanthanide metal is a nitrate.

4. The preparation method according to claim 1, characterized in that: In step 1), the ammonium salt of molybdenum acid is ammonium molybdate.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step 1), the amount of the soluble salt of cobalt added is 2%-4% of the mass of the catalyst calculated as cobalt oxide, the amount of the soluble salt of the lanthanide metal added is 0.5%-1.5% of the mass of the catalyst calculated as its oxide; the amount of the ammonium salt of molybdenum added is 6.5%-9.0% of the mass of the catalyst calculated as molybdenum oxide.

6. The preparation method according to claim 1, characterized in that: In step 2), the pH of the calcium-montmorillonite is 7.5-8.

5.

7. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of magnesium oxide to aluminum oxide added is 1:2.0-4.

5.

8. The preparation method according to claim 1, characterized in that: The binder is citric acid, and the amount of the binder added is 3%-5% of the mass of the catalyst.

9. The preparation method according to claim 1, characterized in that: The calcination time is 2-4 hours.

10. The sulfur-resistant shift catalyst prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-thermal-conductivity sulfur-tolerant shift catalyst as well as preparation method and application thereof

    CN116060071A

  • Difunctional sulfur-tolerant shift catalyst and preparation method thereof

    CN116116424A

  • High-temperature type catalyst for methane synthesis, preparing method and methane synthesis method

    CN103962145A

  • Sulfur-tolerant shift catalyst and preparation method thereof

    CN104248961A

  • Demercuration adsorbent based on pillared montmorillonite, preparation method and application thereof

    CN105664838A